How to Create Augmented Reality (AR) Applications Using Unity and Vuforia Engine to Teach Basic Algorithm Concepts: Step-by-Step Procedure and Bibliometric Analysis - Al Husaeni, Dwi Novia; Munir, M.; Rasim, R. (Indonesian journal of teaching In science, 2024)
Increasingly developing technology causes the need for more interactive and interesting learning methods to increase. Therefore, this research was carried out to provide step by step how to develop Augmented Reality (AR) applications using Unity and Vuforia Engine. The Research and Development method was used in this research to document each step in the AR application development process in Unity with the Vuforia Engine. Apart from that, bibliometric analysis was carried out in this research to determine research trends regarding AR. Selecting the Unity application and Vuforia Engine made it easier to develop AR applications because the steps involved are not too complicated and many features can be accessed for free. Based on the results of bibliometric analysis, publications regarding AR are increasing every year, especially during the 2014-2024 period, with the peak of publications occurring in 2023, reaching 6,835 publications. This research can help educators in creating innovative and creative learning media, especially by utilizing AR technology.